Answer:
5/6
Step-by-step explanation:
it is already written as a fraction.
do you mean as a decimal???
Let the 1st number be x; 2nd number be y; 3rd number be z.
x + y + z = 79
x = number we are looking for.
y = x * 5 ==> 5 times the first
z = x + 16 ==> 16 more than the first
Therefor,
x + (x * 5) + (x+16) = 79
1st step, multiply the 2nd number: x * 5 = 5x
x + 5x + x + 16 = 79
Add all like numbers:
7x + 16 = 79
To get x, transfer 16 to the other side and change its sign from positive to negative.
7x = 79 - 16
7x = 63
To get x, divide both sides by 7
7x/7 = 63/7
x = 9
To check. Substitute x by 9.
x + (x * 5) + (x+16) = 79
9 + (9 * 5) + (9 + 16) = 79
9 + 45 + 25 = 79
79 = 79 equal. value of x is correct.
Answer:
mhmm
Step-by-step explanation:
Answer:
f(-3) =16
Step-by-step explanation:
f(x) = -5x + 1
f(-3) means let x=-3
Substituting x=-3 into the equation
f(-3) = -5 (-3) +1
Multiplying -5 and -3
f(-3) = 15+1
f(-3) =16
The correct answer is C, outcomes